2018
DOI: 10.3201/eid2405.171569
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Oropouche Virus from Febrile Patient, Ecuador

Abstract: We report identification of an Oropouche virus strain in a febrile patient from Ecuador by using metagenomic sequencing and real-time reverse transcription PCR. Virus was isolated from patient serum by using Vero cells. Phylogenetic analysis of the whole-genome sequence showed the virus to be similar to a strain from Peru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 10 publications
1
31
1
2
Order By: Relevance
“…An existing S segment assay (7) failed to detect OROV RNA in an Ecuadorian clinical sample that tested positive by both metagenomic sequencing and virus isolation ( Figure 1) (6). The reverse primer (OROV R) (7) had two mismatches to the novel OROV/EC/Esmeraldas/087/2016 sequence.…”
Section: Development Of An Orov Rrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…An existing S segment assay (7) failed to detect OROV RNA in an Ecuadorian clinical sample that tested positive by both metagenomic sequencing and virus isolation ( Figure 1) (6). The reverse primer (OROV R) (7) had two mismatches to the novel OROV/EC/Esmeraldas/087/2016 sequence.…”
Section: Development Of An Orov Rrt-pcrmentioning
confidence: 99%
“…Metagenomic sequencing (untargeted sequencing of all genetic material in a sample) is an attractive alternative to conventional molecular detection methods as it does not require prior knowledge of pathogen genome sequences. For example, an established OROV rRT-PCR (7) was unable to detect OROV in the plasma of an Ecuadorian febrile patient who tested positive using metagenomic sequencing and virus isolation (6). This highlights the potential for misdiagnosis when screening for pathogens that lack a large collection of reference sequences on which to base targeted amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Six strains of OROV were isolated independently via one passage in Vero cells, from febrile patient sera sampled in 2016 in the Esmeraldas region of Ecuador. RNA was extracted and six complete genome sequences were generated using a metagenomic approach as described previously (14). Briefly, cDNA was prepared using a Sequence Independent Single Primer Amplification (SISPA) approach (27), cDNA sequencing libraries were prepared using the Nextera XT Kit (Illumina), and sequencing was performed on a MiSeq (Illumina) using 150 nucleotide paired-end runs.…”
Section: Sampling and Sequencing Of Orov Isolates From Ecuadormentioning
confidence: 99%
“…Our results show a complex and dynamic picture of the evolution of OROV in the Americas, shaped by reassortment, spatial structure, and natural selection. Our report incorporates new OROV genome sequences obtained from febrile patients in the province of Esmeraldas in northern Ecuador, representing the first direct detection and whole genome sequencing of the virus in the country (14). Previous prospective studies have suggested that OROV may have been circulating in both the coastal and Amazonian provinces of Ecuador (18,70) shown for each plot.…”
Section: Structural Analysis Of Orov Proteins and Sites Under Selectionmentioning
confidence: 99%
See 1 more Smart Citation